Healthy Settlements with Septic Tanks and High Groundwater Table for Waste Management - Kadir, Ishak; Kotta, M. Husni; Ma’ruf, Annas; Lawelendo, Lawelendo; Rachman, Ranno Marlany; Ahdiyani, Wisdha (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
The KKN-Thematic Community Service Program in Leppe Village, Soropia District, Konawe Regency, focuses on enhancing environmental health by implementing adaptive septic tanks in areas with high groundwater tables. The village, located in a coastal region with high groundwater levels, faces significant challenges in waste management, contributing to groundwater contamination and health issues. This program aims to educate the community on the importance of proper sanitation systems, specifically septic tanks, to prevent waterborne diseases and improve overall public health. Through participatory methods, the program involves residents in the planning, construction, and maintenance of septic tanks designed to withstand high water tables. The community is also trained in regular maintenance, ensuring long-term sustainability of the systems. The project is part of a broader effort to improve the quality of life in rural coastal areas by promoting hygienic practices and environmentally friendly waste management solutions. The outcomes of this initiative include increased awareness, improved sanitation infrastructure in the village, and the establishment of a replicable model for other coastal areas. The project has fostered collaboration between local authorities, academic institutions, and the community, laying the groundwork for ongoing environmental health improvements in the region.